Not All Dry Eye in Contact Lens Wear Is Contact Lens–Induced. Issue 4 (July 2020) - Molina, Karen; Graham, Andrew D.; Yeh, Thao; Lerma, Mariel; Li, Wing; Tse, Vivien; Lin, Meng C.
Abstract : Objectives: To compare subjective and clinical outcomes in three study groups: (1) asymptomatic contact lens (CL) wearers (ASYM); (2) symptomatic CL wearers who become asymptomatic on lens removal; and (3) symptomatic CL wearers who do not resolve on lens removal. Methods: Ninety-two subjects completed the Berkeley Dry Eye Flow Chart with and without lenses, ocular surface examinations, and a battery of questionnaires. Results: Thirty-seven subjects (40%) were ASYM, 30 (33%) had contact lens–induced dry eye (CLIDE), and 25 (27%) had underlying physiological DE. Visual Analog Scale ratings, OSDI score, and SPEED score were significantly better for the ASYM group ( P <0.001) but did not distinguish CLIDE from DE. The DE group was significantly worse than CLIDE and ASYM, which were similar, in precorneal noninvasive tear breakup time (8.2 sec DE vs. 12.3 sec CLIDE and 14.3 sec ASYM; P =0.002), anterior displacement of the Line of Marx ( P =0.017), and superior conjunctival staining ( P =0.001). Conclusions: Many CL wearers presenting with dryness symptoms have an underlying DE condition and will not respond to treatments aimed at changing lenses or solutions. Contradictory results from research studies of DE in CL wearers could be due in part to a failure to distinguish subjects with symptoms due specifically to CL wear from those whose symptoms have underlying causes unrelated to CL wear.